An evaluation of the Palani Taluk groundwater quality and its pertinence for agricultural and drinking water in Tamil Nadu, India scarcity problems - Balasubramanian, Shanmuharajan Meenakshi; Bhaskar, Aparna S. (Brawijaya University, 2025)
The groundwater quality and its appropriateness for consumption and farming applications were studied in Palani Taluk, Dindigul District, Tamil Nadu, India. Groundwater is essential for human existence and agriculture; nevertheless, it has been subjected to a plethora of factors, including overexploitation, land use alterations, and climatic variations that deteriorate quantity and quality. A total of groundwater samples were collected and analyzed during pre-monsoon and post-monsoon seasons for the evaluation of the physico-chemical parameters, major ion chemistry, and irrigation suitability indices. The results indicated that electrical conductivity (EC) possessed a strong positive correlation with several parameters prominent in salinity-related water quality degradation. The pre-monsoon samples statistically indicated a lower quality than the post-monsoon samples, but within permissible limits for consumption and irrigation in most instances. Total hardness (Th) and total dissolved solids (TDS) show several to be ranged from hard to very hard in the pre-monsoon season. Gibbs plot analysis indicated that only one or two samples were located in the evaporation dominance zone, whereby contamination through surface activities like irrigation, return flow, and domestic discharge has remained minimal. Most of these samples were rated as good for irrigation in almost all soils, except for a few with medium to high salinity hazards. The study overall showed that groundwater in the region has been mainly suitable for drinking and agricultural uses, with seasonal variations affecting quality, stressing the need for continuous monitoring to reduce decay risks.